Knowledge, attitude and practice among mothers of under five children regarding immunization in a clinic of a private medical college and hospital, Bhubaneswar - Sarangi, Lisa; Panigrahi, Rakesh; Samantara, Chandan; Acharya, Motikrishna; Sahoo, Sumeet Prakash; Gupta, Monica; Sabat, Sunaina; Bilung, Mukesh Kumar; Sucharita, Sushree Soumya (International Journal Of Community Medicine And Public Health, 2023)
Background: Immunization stands as a vital bulwark against vaccine-preventable diseases, especially for children under the age of 5. Cross-sectional study into the knowledge, attitude, and practices (KAP) of mothers concerning childhood immunization and the interplay of sociodemographic factors on immunization practices required. Methods: A descriptive cross sectional study was conducted in an immunization clinic at a private medical college and hospital in Bhubaneswar for a total period of 4 weeks). A population purposive sampling technique was used for this study enlisting 70 mothers with children under 5 years old. Results: The majority of mothers had attained secondary-level education, and significant proportion being homemakers (75.7%). An overwhelming percentage (97.5%) of mothers exhibited a positive attitude towards vaccination, considering it beneficial and safe for their children. However, some exhibited gaps in knowledge concerning the significance of vaccinating from the day of birth and vaccine-related contraindications (24.29%). Crucially, 97.5% of the children had received all mandatory childhood vaccines, and all mothers adhered to the vaccination schedule outlined in the NIS. Socio-demographic factors, such as maternal age and literacy status, are determinants of knowledge about immunization. Younger mothers and those with higher educational attainment were more likely to possess a better understanding of childhood immunization. Conclusions: This study underscores the pivotal role of maternal KAP in ensuring successful immunization for children under 5. The findings advocate for targeted awareness campaigns and interventions aimed at enhancing maternal knowledge, particularly among younger and less educated mothers.